Soil Fertility Properties and Rice Biomass Production Under Three Rice Farming Systems at Vertisols Sambung Macan Sub District, Sragen Regency - . Sukristiyonubowo; Damasus Riyanto; Sugeng Widodo (JOURNAL OF TROPICAL SOILS, 2019)
The farmers realize that green revolution technology with high inputs is no longer sustainable. They want to move to other rice farming systems. The aim of research was to study soil chemical-physical characteristics and rice productions under  three  rice farming systems. This study was conducted in Vertisols at Sambung Macan Sub District, Sragen Regency, arranged in a randomized complete block design with three replications and as the treatments was an organic, semi organic and conventional rice systems. One kilo gram composites soil  samples of 0-20 cm in depth were collected from five random sampling points of every site and taken in March 2017, before soil preparation. Rice biomass productions namely rice grains, rice straw and rice residues were harvested in the end of June 2017. The results indicated that in organic field, the soil chemical-physical fertility was superior to that of in semi organic and conventional and semi organic system was better than conventional in terms of soil pH, organic C and total N, P and K total, soil bulk density, particle density, soil porosity and permeability. Similar finding was observed for rice biomass productions. The rice grains yields were 7.53 ± 0.85, 6.60 ± 0.15 and 5.77 ± 0.71, rice straw were 7.97 ± 0.47, 7.63 ± 0.21 and 6.93 ± 0.25 and forrice residues were 4.20 ± 0.10, 3.30 ± 0.20 and 3.25 ± 0.35 Mgs ha-1 season-1 in organic, semi organic and conventional systems, respectively.Compared to the conventional system, the organic increased about 31 %, 15% and 29 % for rice grains, rice straw and rice residues, respectively. Comparing semi organic to conventional, the improvement was 14 %, 10 % and 2 % for rice grains, rice straw and rice residues, respectively. This short term research concluded that organic rice farming was superior to both semi organic and conventional systems, but the long term effect of organic need to be further evaluated.